ChemInform Abstract: Domino Reactions Based on Knoevenagel Condensation in the Synthesis of Heterocyclic Compounds. Recent Advances. Issue 17 (28th April 2014) - Voskressensky, Leonid G.; Festa, Alexey A.; Varlamov, Alexey V.
Abstract Review: 66 refs.